Pengaruh Spiritualitas Dan Pengetahuan Perbankan Syariah Pada Loyalitas Nasabah Bank Non Syariah - Maheswari Dewi Ayu Larasati; Luqman Hakim (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
The study was conducted to analyze the influence of spirituality and sharia banking knowledge to the loyalty of customer of non-sharia banks with the aim of knowing whether there are spirituality and sharia banking knowledge affecting the loyalty of customers both either partially and simultaneously. Research conducted using quantitative research with multiple linear regression analysis. The data collection used is purposive sampling with the number of samples by 385 respondents. The results of the research show that spirituality has a significance value of 0.001 <0.05, so that spiritual variables may affect customer loyalty. Sharia banking knowledge has significance value of 0.000 <0.05, so that the shariah bloody knowledge variable can affect customer loyalty. Spirituality and knowledge of sharia banking simultaneously can affect the customer loyalty because it has a significance value of 0.000 <0.05. The customer loyalty variable can be interpreted by the spirituality variable and sharia banking knowledge of 0.131 or 13.1%, while 86.9% can be interpreted with the variables outside the research. The results of the analysis of the conclusion that spirituality may affect the loyalty of customer of non-sharia banks, sharia banking knowledge can also affect the loyalty of customer of non-sharia banks, as well as spirituality and knowledge of sharia banking may affect the loyalty of customer of non-syariah bank simultaneously.